Care Seeking Behaviour and Barriers to Accessing Services for Sexual Health Problems among Women in Rural Areas of Tamilnadu State in India. (20th March 2014) - Puthuchira Ravi, Rejoice; Athimulam Kulasekaran, Ravishankar
Abstract : Background . Sexually transmitted infections (STIs) may be either asymptomatic or symptomatic. Regardless of the presence or absence of symptoms all STIs can lead to major complications if left untreated. Objective . To assess the care seeking behaviour and barriers to accessing services for sexual health problems among young married women in rural areas of Thiruvarur district of Tamil Nadu state in India. Methods . A community based cross-sectional study was conducted in 28 villages selected using multistage sampling technique for selecting 605 women in the age group of 15–24 years during July 2010–April 2011. Results . The prevalence rate of reproductive tract infections (RTIs) and STIs was observed to be 14.5% and 8.8%, respectively, among the study population. Itching/irritation over vulva, thick white discharge, discharge with unpleasant odor, and frequent and uncomfortable urination were most commonly experienced symptoms of sexual health problems. Around three-fourth of the women received treatment for sexual health problems. Perception of symptoms as normal, feeling shy, lack of female health workers, distance to health facility, and lack of availability of treatment were identified as major barriers for not seeking treatment for RTIs/STIs. Conclusion . Family tradition and poor socioeconomic conditions of the family appear to be the main reasons for not utilizing the health facility for sexual health problems. Integrated approach is strongly suggested for creating awareness to control the spread of sexual health problems among young people.